Twist‐Bend Nematic Glasses: The Synthesis and Characterisation of Pyrene‐based Nonsymmetric Dimers. Issue 5 (3rd February 2021) - Walker, Rebecca; Majewska, Magdalena; Pociecha, Damian; Makal, Anna; Storey, John MD; Gorecka, Ewa; Imrie, Corrie T.
Abstract: A selection of pyrene‐based liquid crystal dimers have been prepared, containing either methylene‐ether or diether linked spacers of varying length and parity. All the diether linked materials, CBO n O.Py ( n =5, 6, 11, 12), exhibit conventional nematic and smectic A phases, with the exception of CBO11O.Py which is exclusively nematic. The methylene‐ether linked dimer, CB n O.Py, with an even‐membered spacer ( n =5) was solely nematogenic, but odd‐members ( n =6, 8, 10) exhibited both nematic and twist‐bend nematic phases. Replacement of the cyanobiphenyl fragment by cyanoterphenyl giving CT6O.Py, gave elevated melting and nematic‐isotropic transition temperatures, and SmA and SmCA phases were observed on cooling the nematic phase. Intermolecular face‐to‐face associations of the pyrene moieties drive glass formation, and all these materials have a glass transition temperature at or above room temperature. The stability of the glassy twist‐bend nematic phase allowed for its study using AFM, and the helical pitch length, PTB, was measured as 6.3 and 6.7 nm for CB6O.Py and CB8O.Py, respectively. These values are comparable to the shortest pitch of a twist‐bend nematic phase measured to date. Abstract : Pyrene‐based liquid crystal dimers containing spacers of varying nature, length, and parity were prepared. Some of these materials have a glass transition temperature at or above room temperature, yielding a highly stable twist‐bend nematic phase. The stability of this glassy phase allowed for its study using AFM, and these materials possess one of the shortest pitches of a twist‐bend nematic phase measured to date.